The Jurisdictional Implications on Default of the Parties to Trademark License Agreements Made before a Notary - Muhammad Zaenal Luthfi (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
This study aims to identify and analyze the juridical implications of the parties' default in the trademark license agreement made before a notary, to identify and analyze the legal remedies for the parties' default in the trademark license agreement made before a notary. The research approach method used in this thesis is a normative juridical legal research method. Specifications This study uses a description of the analysis. Sources of data come from primary data which includes Act No. 20 of 2016 concerning Brands and Geographical Indications, PP No. 36 of 2018 concerning the recording of IPR License Agreements, Act No. 2 of 2014 in conjunction with Act No. 30 of 2004 concerning the position of a Notary, as well as secondary data containing books and other supporting documents. Data collection methods include library research, Document Study. The data analysis method used in analyzing the data is qualitative analysis. The results of the study indicate that in a trademark license agreement made before a notary, it is obligatory to submit an application for registration to the Ministry of Law and Human Rights in order to obtain legal protection. However, if the license agreement is not registered, the license agreement is only binding on the parties who entered into the license agreement and in the event of a default, the license agreement can be canceled or null and void and has no impact on third parties. Legal remedies if there is a dispute in the trademark license agreement, namely by litigation and non-litigation.